Optimization of Capital Expenditure and Goods and Services Expenditure for Human Resource Development in Health, Education, and Economic Sectors: A Study in Gerbangkertosusila - Mardianto, Reyhan Andra; Fazaalloh, Al Muizzudin (Journal of Development Economic and Social Studies, 2025)
This study analyzes the impact of regional government spending on the Human Development Index (HDI) in seven districts/cities within the Gerbangkertosusila region and 38 districts/cities in East Java from 2017 to 2023. The main focus is on the influence of capital expenditure and spending on goods and services in the health, education, and economic sectors. The data used in this study comes from the East Java Central Bureau of Statistics (BPS) and regional financial reports published by the Directorate General of Fiscal Balance (DJPK) of the Ministry of Finance. The study aims to provide recommendations for the government in formulating policies and developing more effective strategies to enhance public welfare by optimizing expenditures in the relevant sectors. The analysis method employed is panel data regression. The results indicate that in the Gerbangkertosusila region, spending in the health and economic sectors has a positive and significant impact on HDI, while education spending does not show a significant effect. Meanwhile, in the 38 districts/cities of East Java, spending in all three sectors—health, education, and the economy positively and significantly influences HDI.